ADSORPSI EMAS(III), TEMBAGA(II), NIKEL(II) PADA MAGNETIT TERLAPIS HIBRIDA AMINO SILIKA - , MUHAMMAD TAUFIQ T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Selective adsorption of Au(III) in multimetal systems Au 3+ /Cu 2+ /Ni 2+ on amino-silica hybrid coated magnetite (MHAS) has been studied. MHAS was synthesized via sol-gel process using magnetite that was obtained through coprecipitation of Fe 2+ /Fe 3+ salts mixture with NH4OH as precipitating solution, sodium silicate solution of rice husk ash as a precursor and 3- aminopropyltrimethoxysilane (APTMS) as a source of amino. MHAS was characterized by Fourier Transform Infrared (FTIR) Spectrophotometer and X Ray Diffraction (XRD). Optimization of Au (III) adsorption was carried out as function of pH, contact time and concentration of ion. Adsorption kinetics was determined by pseudo-first order and pseudo-second order model, while the adsorption isotherm was analyzed studied by the Langmuir and Freundlich models. The adsorbed metal ions Au(III), Cu(II) and Ni(II) quantitatively calculated based on the difference of metal ion concentrations before and after adsorption that were analyzed by Atomic Absorption Spectrophotometer (AAS). Similar work conducted for multimetal (Au 3+ /Cu 2+ /Ni 2+ ) system for evaluating the selectivity of adsorbent. FTIR characterizations showed that MHAS has been successfully synthesized, indicated by the appearance of characteristic frequency at 570 cm -1 was stretching vibrations of Fe-O-Si and frequency at 3424 cm -1 was stretching vibrations of N-H. The XRD showed that coated with magnetite was not change the crystallinity. Adsorption kinetics studies showed that the adsorption of Au(III) on MHAS fit to pseudo-second order model with adsorption rate constant was 1.21x10 -3 g.mg -1 min -1 . MHAS adsorbent showed a linear plot of Langmuir isotherm model with adsorption capacity of Au(III) was 102,04 mg/g. Adsorption on multimetal showed that Au(III), Cu(II), Ni(II) were adsorbed with chemical interaction on the MHAS with capacity adsorption of Au(III) was higher than that of Cu(II) and Ni(II). MHAS has high enought selectivity for Au(III) toward Cu(II) and Ni(II) ions.